EFEKTIVITAS MODEL CONTEXTUAL, TEACHING AND LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN PENALARAN MATEMATIS PADA MATERI PERSAMAAN LINIER SATU VARIABEL KELAS VIII SMP NEGERI 12 MEDAN T.A. 2023/2024 - Lumban Toruan, Nia Natasha; Tambunan, Hardi; Simanjuntak, Ruth Mayasari (Jurnal Curere, 2024)
This study aimed to determine the effectiveness of the contextual teaching and learning model on students' problem-solving skills and mathematical reasoning abilities in linear equations with one variable. Furthermore, this study sought to investigate the level of effectiveness of the contextual teaching and learning model in enhancing students' problem-solving skills and mathematical reasoning abilities. The research employed a quasi-experimental design with the entire population of grade VIII students serving as the population. Cluster random sampling was used to select the sample. The hypothesis was tested using the F-test. The results showed that (1) the contextual teaching and learning model was effective in improving students' problem-solving skills; (2) the effectiveness of the contextual teaching and learning model in enhancing students' problem-solving skills was categorized as high; (3) the contextual teaching and learning model was effective in improving students' mathematical reasoning abilities; and (4) the effectiveness of the contextual teaching and learning model in enhancing students' mathematical reasoning abilities was categorized as moderate.